2014
DOI: 10.1177/0300060513505813
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin 10 gene polymorphisms and risk of type 2 diabetes mellitus in a Chinese population

Abstract: Objective: To investigate the relationship between the interleukin 10 (IL10) gene single nucleotide polymorphisms (SNP) À1082 G/A (rs1800896), À819 T/C (rs1800871) and À592 A/C (rs1800872) and risk of type 2 diabetes mellitus in a Chinese population. Methods: This case-control study recruited patients with type 2 diabetes mellitus and healthy control subjects. Genotyping of the À1082 G/A (rs1800896), À819 T/C (rs1800871) and À592 A/C (rs1800872) SNPs was conducted and genotype frequencies were compared between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 22 publications
1
27
0
1
Order By: Relevance
“…Additionally, a case-control study conducted by Bai and cols. (34) found higher risk for T2DM development associated with -1082 GA+GG and -592 AC+AA genotypes. These conflicting results are probably related to the sample size and different genetic background of the populations.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Additionally, a case-control study conducted by Bai and cols. (34) found higher risk for T2DM development associated with -1082 GA+GG and -592 AC+AA genotypes. These conflicting results are probably related to the sample size and different genetic background of the populations.…”
Section: Discussionmentioning
confidence: 80%
“…Some studies have investigated the association among TNF-α, IL-6, and IL-10 gene polymorphisms with metabolic diseases (17)(18)(19)(20)(21)(22)(23)(24)(25). Despite these reports examining the association of inflammation markers and SNPs in cytokine genes, much controversy remains as to their role in diabetes occurrence (26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Amre et al (2009) conducted a study on 270 patients with Crohn's disease and 336 control subjects, and reported that IL-10 -819C/T variants contributed to the onset of Crohn's disease. Several studies have reported the possible correlation between polymorphisms in IL-10 and the onset of type 2 diabetes mellitus, but with conflicting results (Ezzidi et al, 2009;Saxena et al, 2012Saxena et al, , 2013Yin et al, 2013;Bai et al, 2014;Chang et al, 2005). Chang et al (2005) reported that IL-10 polymorphisms could determine diabetic susceptibility in a Taiwanese population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Saxena et al (2012Saxena et al ( , 2013 reported that Indian patients harboring the IL-10 -592C/A polymorphism displayed a greater risk of developing type 2 diabetes mellitus compared to that by the controls. Bai et al (2014) reported that the IL-10 -592C/A and -1082G/A polymorphisms increased the risk of type 2 diabetes mellitus in a Chinese population. A recent meta-analysis comprising 10 studies indicated that only the IL-10 -1082G/A polymorphism contributed to the onset of type 2 diabetes mellitus, while the IL-10 -819C/T and -592C/A polymorphisms did not (Hua et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation